Who would be targeted by increasing the legal age of sale of cigarettes from 18 to 21? A cross‐sectional study exploring the number and characteristics of smokers in England. (10th February 2021) - Beard, Emma; Brown, Jamie; Jackson, Sarah E.; West, Robert; Anderson, Will; Arnott, Deborah; Shahab, Lion
Abstract: Aims: To establish the number of smokers in England who would be targeted by increasing the age of sale of cigarettes from 18 to 21 years and to assess the smoking and socio‐demographic profile of those smokers. Design and setting: Nationally representative cross‐sectional survey of adults in England conducted between January 2009 and July 2019. Participants: A total of 219 720 adults. Measurements: All participants reported their current smoking status and socio‐demographic characteristics (i.e. age, gender, home ownership, social grade and ethnicity). Smokers reported motivation to quit, urges to smoke and the Heaviness of Smoking Index (HIS). Weighted prevalence statistics were calculated. Multinomial regression and logistic regression were used to assess differences in smoking characteristics among smokers and socio‐demographic characteristics relative to non‐smokers. Findings: The prevalence of smoking between January 2009 and July 2019 was highest among those aged 21–30. In 2019, 15.6% [95% confidence interval (CI) = 12.8–18.8%] of 18–20‐year‐olds reported smoking, which is estimated to represent 364 000 individuals in England. Relative to smokers aged 18–20, older smokers (aged 21+) had a higher motivation to quit smoking [odds ratios (ORs) = 1.40–1.45 range] and higher nicotine dependency as measured by urges to smoke (ORs = 1.06–1.24 range) and HSI (ORs = 1.05–2.85 range). Compared with non‐smokers aged 18–20, smokers in this age group had lower odds of being female (OR = 0.89) and higher odds of being of white ethnicity (OR = 2.78) and from social grades C1–E (lower social grades) compared with AB (higher social grades) (OR = 1.19–1.83 range). Conclusion: Increasing the age of sale of cigarettes to 21 years in England would currently target approximately 364 000 lower dependent smokers from more disadvantaged backgrounds aged 18–20, who have less motivation to quit.